"I'm Gonna Shake and Shimmy" or may be not:choreographing Hairspray – a Practice as Research project. Issue 1 (2nd January 2020) - Lidbury, Clare
ABSTRACT: Using practice as research as my methodology I examine whether it is possible to choreograph Hairspray - the Musical while staying true to the movement principles developed by Kurt Jooss and Sigurd Leeder in the Jooss-Leeder Method. In discussing the process and the product I explore also the difficulties in choreographing for, and teaching the dances to, a cast of 15–18-year-olds in a school where there is no dance in the curriculum at this level. I conclude that selected Jooss-Leeder movement principles provide a useful framework for choreographing the musical numbers, that Leeder's organic teaching process is effective for these novice dancers and that a lack of dance experience does not preclude a successful production.